2017
DOI: 10.1007/s10549-017-4178-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumor DNA methylation patterns associated with smoking in the Carolina Breast Cancer Study

Abstract: Purpose Tobacco smoking is a risk factor in several cancers, yet its roles as a putative etiologic exposure or poor prognostic factor in breast cancer are less clear. Altered DNA methylation contributes to breast cancer development and may provide a mechanistic link between smoking and gene expression changes leading to cancer development or progression. Methods Using a cancer-focused array, we examined methylation at 933 CpGs in 517 invasive breast tumors in the Carolina Breast Cancer Study to determine whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 75 publications
(91 reference statements)
0
13
0
1
Order By: Relevance
“…Since no information regarding the current and past smoking history of our patients was available, smoking was not included as a covariate in the model which is a limitation of our data. A larger follow up study should include smoking data since tobacco smoke is reported to alter the methylation state of tumoral DNA [ 42 ]. Using our current cohort, the number of samples did not allow sufficient power of analysis based on TNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…Since no information regarding the current and past smoking history of our patients was available, smoking was not included as a covariate in the model which is a limitation of our data. A larger follow up study should include smoking data since tobacco smoke is reported to alter the methylation state of tumoral DNA [ 42 ]. Using our current cohort, the number of samples did not allow sufficient power of analysis based on TNM staging.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ER − basal-like intrinsic subtype is more prevalent among African-American and younger patients [7], carries a high frequency of p53 gene mutations [39, 40] and is relatively deficient in DNA repair and more genetically unstable [41]; it seems plausible that the insult of tobacco smoke chemicals could potentiate this instability, leading to more recurrences. The smoking-breast cancer mortality associations may also be mediated by smoking-induced alterations in methylation of breast tumor DNA; a recent study found that current smokers with hormone receptor negative breast tumors exhibited primarily CpG hypomethylation compared to never smokers [42]. From studies of head and neck and lung cancers, it has also been hypothesized that smoking may reduce treatment efficacy, in particular responses to radiation and chemotherapy treatments [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is responsible for ~3.4 million deaths worldwide [ 22 ]. Some of the well-known causes for cancer disease are smoking (causing lung [ 23 ], breast [ 24 ], and ovarian cancer [ 25 ]), being overweight or obese (associated with 13 types of cancer disease, such as breast cancer, kidney, womb and bowel cancers), intake of processed meat [ 26 ], radiation (causes skin cancer) [ 27 ], family history, stress, environmental factors, and chance [ 28 ].…”
Section: Cancermentioning
confidence: 99%